Apoio matricial : um modo ampliado de cuidar da saúde do idoso no município de Vitória - Nascimento, Olga Maria do (2016)
This work analyses the contribution of the Matrix support on eldercare regarding the qualifying demand of Basic Healthcare Units for specialized treatment in the Elderly Care Reference Center, as well as the improvements in the access of the fragile elderly to this service. The Matrix support methodology has been implemented by the Elderly Care Reference Center team, at the end of 2008, with the purpose of providing specialized backup both for assistance-related issues and for the pedagogical support to the reference teams in the Basic healthcare units. The dissertation presents Elderly Care Reference Center’s implementation process as a service within the municipal network of Vitoria aimed at the elderly care. The theoretical development draws on the Matrix support concept as a management technology, in order to explain how such expedient take place in the work processes in healthcare. The research covers the period between October 2007 and December 2008, prior to the Matrix support; and the period between January and December 2013, after five years of the Matrix support implementation. It also comprises the data related both to the five Basic healthcare units which first settled the Matrix support and to the interviews conducted with professionals from Elderly Care Reference Center’s basic team, which includes the physician, the nurse and the social assistant. The data collected in this research have been analyzed and classified based on the following categories: the origin of the Basic healthcare unit, age group, gender, reasons for referral. The outcome of this study points out to a shift in the descriptions regarding the reasons for referral, thereby including data expressing the expansion of the clinic and highlighting a shift from a disease-based to a functional capacity paradigm. Such results showcase the Matrix support potential in an extended eldercare. It can be concluded that expanding the eldercare network, especially to the elderly more subject to enfeeblement, is a necessity. It is necessary to intensify actions so that the Primary Health Care teams feel themselves able to provide greater care to this public. The Matrix support tool is one of the possibilities which contribute to expand the elderly healthcare. It must be also emphasized the necessity to provide for the creation of other services, regarding the rapid aging of our population.